The Effect of Microteaching and Students Self-Efficacy on Readiness to Teach Economics Lessons in School Field Experience (SFE) Program - Dini Octoria; Ananda Fitri Nurhidayati; Tya Wahyu Nofitri (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2026)
Teaching readiness is one of the benchmarks for the success of students in the faculty of teaching and education because teaching is a practical skill that must be realized when students pursue the School Field Experience (SFE) Program. This research was conducted to determine microteaching and student self-efficacy in providing partial and simultaneous effects on the teaching readiness of economics education studies. A quantitative approach was used as the research methodology, with a population of all students in the Economics Education Study Program who had taken the microteaching course, resulting in a sample size of 120 students. In line with the saturation sampling technique, the entire population was selected as respondents due to the relatively small number of respondents and their ability to provide information. A questionnaire was used to collect all data, validated with Confirmatory Factor Analysis and Cronbach Alpha for reliability. Data were analyzed using descriptive and inferential statistics, including a t-test to determine partial effects and an F-test to determine simultaneous effects. The results showed that microteaching and student self-efficacy had a positive effect on the readiness to teach economics lessons, both partially and simultaneously. The implications of this study are aimed at students to increase their self-efficacy by adapting their learning strategies and fully engaging in both theoretical and practical pedagogical learning.